Use of Electronic Media and its Association with Teenager's Behavior: An Analytical Cross-sectional Study in Community Clinics of Karachi - Anjarwala, Zainab Mohammad; Beg, Anum Arshad; Ali, Yousaf; Karmani, Veena Kumari; Ali, Sundus; Kanwal, Sidra (Journal of Liaquat University of Medical & Health Sciences, 2023)
OBJECTIVE: To estimate the proportion of electronic media usage among teenagers and identify the association between behavior and the use of electronic media. METHODOLOGY: An analytical cross-sectional study conducted from December 2021 to February 2022. A sample of teenagers (n=340) were selected from primary care clinics of Chanesar Goth and Hijrat Colony, Karachi. Participants were questioned regarding their daily usage of media. Strengths and Difficulties Questionnaire was administered to assess the behavior. Data was analyzed using SPSS 23. RESULTS: 350 teenagers were enrolled in the study, and the gender distribution was almost equal. Daily usage of media included Television(88.9%), videogames(47.4%), computer/laptop(79%), mobile phone(90.3%) and tablet(20.9%). The content viewed were movies (68.9%), Facebook (72%) and Chats/WhatsApp (76.6%). The mean of total difficulty score in our study population was 19.1 (SD: 4.8). On multivariate analysis, higher difficulty score was positively associated with increasing age (Beta: 0.428, 95% Cis: 0.070 -0.785, p-value: 0.019) and total screen time (Beta: 0.003, 95% Cis: 0.001 -0.005, p-value: 0.036) while difficulty score was negatively associated with male gender (Beta: -1.223, 95% Cis: -2.441 -- -0.005, p-value: 0.049). CONCLUSION: Our population's media exposure and difficulty scores are higher than those of other populations. Media exposure needs to be reduced to control psychosocial problems.